Construction of Fishermen's Purity with Limitations: Pabagang Study on Balang Caddi Island, Pangkep-South Sulawesi - Fatimah hs; Iin Parninsih (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2022)
One of the biggest challenges for fisherman workers is to live a religious life within limitations, such as religious knowledge and worship facilities, as experienced by Pabagang on Balang Caddi Island, Pangkep-South Sulawesi. This study discusses Muslim fishermen on Balang Caddi Island by referring to the question of how is the piety construction of Pabagang Muslim fishermen on Balang Caddi Island amid its limitations. This study is field research, which means that the primary source of this study comes from field data such as interviews, observations, and documentation. At the same time, secondary sources come from articles, websites, dissertations, and others that discuss the issues being studied. These various sources are managed using the descriptive-analytical method. From this, this study concludes that the construction of Pabagang's religious life leads to social piety, which contributes to the ritual piety of the people of Balang Caddi Island. This phenomenon cannot be separated from the significance of its social role in religious life on Balang Caddi Island, which is heavily influenced by the religious model of pesantren Darul Da'wah wal Irsyad (DDI) Mangkoso. Pabagang's religious life is common in Indonesian society, where workers (whatever their occupation) are not active in ritual piety but in social piety. Therefore, any worker, who earns a lawful living, needs to be seen as equal to other people, especially to achieve a complementary society.